2013
DOI: 10.1130/g34187.1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope systematics of a euxinic, low-sulfate lake: Evaluating the importance of the reservoir effect in modern and ancient oceans

Abstract: The sulfur (S) isotope difference between sedimentary sulfate and sulfi de phases preserved in sedimentary rocks (Δ 34 S) has been utilized to reconstruct marine sulfate concentrations and inferentially the redox evolution of Earth's surface. These interpretations are largely based on experimental studies that indicate that microbial sulfate reduction is accompanied by a substantial kinetic isotope effect (up to 66‰), but only at sulfate concentrations >~200 µM. In this study, we examine S isotope systematics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 22 publications
2
58
1
Order By: Relevance
“…(<10&) in Archean sedimentary pyrites was due to the suppression of biologically imparted S isotope fractionation at low sulfate levels (>200 lM; Habicht et al, 2002), subsequent work has shown that MSR can impart substantial S isotope fractionations even at very low sulfate concentrations (Nakagawa et al, 2012;Gomes and Hurtgen, 2013;Crowe et al, 2014). Yet, it is still likely that Archean sulfate levels were low.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…(<10&) in Archean sedimentary pyrites was due to the suppression of biologically imparted S isotope fractionation at low sulfate levels (>200 lM; Habicht et al, 2002), subsequent work has shown that MSR can impart substantial S isotope fractionations even at very low sulfate concentrations (Nakagawa et al, 2012;Gomes and Hurtgen, 2013;Crowe et al, 2014). Yet, it is still likely that Archean sulfate levels were low.…”
Section: Introductionmentioning
confidence: 87%
“…The mean e SR value at Lake Matano was determined by a reactive-diffusion model (Crowe et al, 2014). For Lake McCarrons (Gomes and Hurtgen, 2013) and Lake Fukami-ike (Nakagawa et al, 2012), a Rayleigh fractionation model was used to calculate e SR (after Mariotti et al, 1981). There was not sufficient water column d 34 S data to calculate e SR for Effingham Inlet and Tyro Basin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In laboratory experiments and natural marine and lacustrine systems, volumetric sulfate reduction rates scale primarily as a function of the availability of sulfate relative to common electron donors like organic carbon Goldhaber and Kaplan, 1975;Sim et al, 2011b;Leavitt et al, 2013). Indeed, sulfate can be non-limiting even in environments with as little as µM sulfate (Nakagawa et al, 2012;Gomes and Hurtgen, 2013;Crowe et al, 2014;Bradley et al, 2015), assuming organic matter is more limiting to allow a fractionation to occur (Wing and Halevy, 2014;Bradley et al, 2015). Constrained whole cell (in vivo) laboratory experiments demonstrate that when electron donors are limiting, the magnitude of fractionation between sulfate and sulfide ( 34 ε) carries a nonlinear inverse relationship with cell-specific sulfate reduction rates (Harrison and Thode, 1958;Kaplan and Rittenberg, 1964;Sim et al, 2011b;Leavitt et al, 2013).…”
Section: Fractionation At the Cellular Scalementioning
confidence: 99%